Representasi Diagram Garis sebagai Solusi Permasalahan Bilangan Bulat pada Siswa Sekolah Dasar - Bambang Hudiono (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: This experimental research has a purpose to describe influence of implementation numbers line variation and skills level on learning outcomes, influence of students’ level skills on students’ representation, and sum of students’ representation in answering mathematic problems. The subjects were fifth grade students at Pontianak city. Results found that implementation of empty lined number should be developed in students as a method for increasing children’s understanding about the whole numbers.